Konstruksi Wacana Genosida dalam Lirik Lagu Rajieen: Analisis Wacana Kritis Teun A.Van Dijk - Labib, Ahmad Jadir (Universitas Al Azhar Indonesia, 2026)
The research is motivated by the escalation of violence following the October 2023 attacks, which triggered a severe humanitarian crisis in Palestine and inspired expressions of solidarity from artists through music. This study aims to examine the discursive construction of genocide in the lyrics of the song Rajieen using Teun A. Van Dijk’s Critical Discourse Analysis. This study employs a qualitative descriptive method. The primary data source is the lyrics of Rajieen obtained from the platform Spotify, consisting of words, phrases, and sentences that represent genocide discourse. Data were collected through intensive reading and analyzed using Van Dijk’s framework, which includes textual structure, social cognition, and social context. The findings show that the macrostructure of the song emphasizes suffering and the threat of mass extermination faced by Palestinian society. At the level of social cognition, the lyrics articulate criticism of global humanitarian double standards. In the broader social context, the song functions as a counter-discourse to dominant media narratives about the Palestine–Israel conflict. These findings suggest that music can serve as cultural advocacy highlighting global human rights violations. Future research should examine audience reception to understand its influence on public perceptions of the Palestine–Israel conflict.Keywords - Discourse, Genocide, Rajieen.